2019
DOI: 10.3390/cells8070756
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Dendritic Cells Are Enriched in Lymph Node Tissue of Early Rheumatoid Arthritis Patients but not in At Risk Individuals

Abstract: Lymph nodes (LNs) are highly organized structures where specific immune responses are initiated by dendritic cells (DCs). We investigated the frequency and distribution of human myeloid (mDCs) and plasmacytoid (pDCs) in LNs and blood during the earliest phases of rheumatoid arthritis (RA). We included 22 RA-risk individuals positive for IgM rheumatoid factor and/or anti-citrullinated protein antibodies, 16 biological-naïve RA patients and 8 healthy controls (HCs). DC subsets (CD1c+ mDCs and CD304+ pDCs) in LN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…We observed an increase in the percentage of pDCs and mDCs in RA patients, consistent with previous reports [ 38 , 39 ]. However, other study showed decreased of DCs in peripheral blood of RA [ 40 ]. It was reported that pre-DCs are expanded in the bone marrow of RA patients, the increase of pre-DCs in the bone marrow shall lead to the increase of DCs in the peripheral blood, which supports our results [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed an increase in the percentage of pDCs and mDCs in RA patients, consistent with previous reports [ 38 , 39 ]. However, other study showed decreased of DCs in peripheral blood of RA [ 40 ]. It was reported that pre-DCs are expanded in the bone marrow of RA patients, the increase of pre-DCs in the bone marrow shall lead to the increase of DCs in the peripheral blood, which supports our results [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the DCs in the pancreatic lymph nodes of type I diabetes patients may have reduced tolerogenic function than those of healthy controls, and there were even differences in lymph node cell composition when correcting for sex and age ( 140 ). T cells, B cells, DCs, and other lymph node cells are also shown to be different in rheumatoid arthritis patients compared to healthy individuals ( 141 143 ). Furthermore, efferocytosis can be defective in patients with autoimmune diseases ( 144 , 145 ) or obese individuals ( 146 ), so for these patients nanoparticles that aim to exploit efferocytosis may not be as effective.…”
Section: Translation To Humanmentioning
confidence: 99%
“…Both dendritic cells (DCs) (25,26) as well as lymph node stromal cells (LNSC) (27,28) have the capacity to induce peripheral tolerance through presentation of peripheral tissue antigens (PTAs) to autoreactive T cells after which these cells undergo clonal deletion, differentiation into a regulatory T cell or become anergic. When studying DC subsets (CD1c + myeloid DCs and CD304 + plasmacytoid DCs) in LN tissue it appeared that frequencies are comparable between RA-risk individuals and healthy controls, but increased in RA patients (29). This may suggest that these DCs are involved in sustaining inflammation during established RA, or that other DC subsets or other antigen presenting cells (APCs) are responsible for the initial break in tolerance.…”
Section: Ln Studies Reveal Immune Cell Activation During the Earliest...mentioning
confidence: 99%